High performance flat sheet forward osmosis membrane with an NF-like selective layer on a woven fabric embedded substrate - Qiu, Changquan (2013)
High performance flat sheet forward osmosis (FO) membranes have been successfully fabricated using Torlon® polyamide-imide (PAI) materials via phase inversion followed by polyelectrolyte polyethyleneimine (PEI) post-treatment to form a nanofiltration (NF)-like rejection layer with positive charges. The structure and charge property of the FO membranes were carefully tailored by optimizing casting conditions and selecting different immersing methods for the post-treatment. Especially, when the PAI micro-porous substrate was embedded with a woven fabric, the enhanced mechanical strength of the membrane made it possible to reduce the thickness of the substrate to 55 μm, which is in favor of high water flux. The resultant membranes can reach a water flux of 29.65 L m− 2 h− 1 with a ratio of salt flux to water flux (Js/Jv) of < 0.8 g L− 1 in the active layer facing draw solution (AL-facing-DS) configuration, or the water flux of 19.2 L m− 2 h− 1 and the Js/Jv of < 0.5 g L− 1 in the active layer facing feed water (AL-facing-FW) configuration using 0.5 M MgCl2 as the draw solution and de-ionized water as the feed water at room temperature.